2021
DOI: 10.1029/2020gl092365
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Carbonate Lithologies in Jezero Crater, Mars

Abstract: Jezero crater is the landing site for the Mars 2020 Perseverance rover. The Noachian‐aged crater has undergone several periods of fluvial and lacustrine activity and phyllosilicate‐ and carbonate‐bearing rocks were formed and emplaced as a result. It also contains a portion of the regional Nili Fossae olivine‐carbonate unit. In this work, we performed spectral mixture analysis of visible/near‐infrared hyperspectral imagery over Jezero. We modeled carbonate abundances up to ∼35% and identified three distinct un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…As indicated by Horgan et al. (2020) and Zastrow and Glotch (2021), the broad absorption feature centered at 1.0 μm is consistent with the presence of olivine, but due to the presence of absorptions at 2.3 and 2.5 μm is also consistent with FeCO 3 , or a mixture of FeCO 3 and olivine (Figure 3e; Figures S1d, S2d, S3c, S4c, S5d and S13 in Supporting Information ). The lack of clear contacts between the ROB unit draping into Jezero crater and the margin fractured unit does favor the interpretation that the 1.0 μm absorption in the margin fractured unit is due to olivine, which is present throughout the ROB unit, or a mixture of olivine and FeCO 3 .…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…As indicated by Horgan et al. (2020) and Zastrow and Glotch (2021), the broad absorption feature centered at 1.0 μm is consistent with the presence of olivine, but due to the presence of absorptions at 2.3 and 2.5 μm is also consistent with FeCO 3 , or a mixture of FeCO 3 and olivine (Figure 3e; Figures S1d, S2d, S3c, S4c, S5d and S13 in Supporting Information ). The lack of clear contacts between the ROB unit draping into Jezero crater and the margin fractured unit does favor the interpretation that the 1.0 μm absorption in the margin fractured unit is due to olivine, which is present throughout the ROB unit, or a mixture of olivine and FeCO 3 .…”
Section: Resultssupporting
confidence: 56%
“…Past research reported that carbonates in the Nili Fossae region—including in Jezero crater—have 2.3 and 2.5 μm absorption minima wavelength positions consistent with Mg‐rich carbonate (Ehlmann, Mustard, Murchie, et al., 2008). The presence of Fe‐rich carbonates in Jezero crater has also recently been proposed based on linear unmixing (Zastrow & Glotch, 2021). In nature, Fe/Mg‐carbonates are a solid solution between FeCO 3 and MgCO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, the lack of clear mineralogical evidence (so far) for local hydrothermal activity at the Oxia Planum landing site is reassuring. However, the large fluvial catchment area in this region may have concentrated organic matter of remote and diverse provenance and carbonate minerals in Jezero Crater could be related to serpentinization (Quantin-Nataf et al 2021;Zastrow and Glotch 2021).…”
Section: Abiotic Organic Matter: Molecular Pseudofossilsmentioning
confidence: 99%
“…2017). Mineral assemblages suggestive of local serpentinization and serpentine alteration occur at several localities on Mars, including Jezero Crater(Ehlmann et al 2010;Michalski et al 2018;Brown et al 2020;Zastrow and Glotch 2021). More generally, the copious production of silica-rich fluids on early Mars is attested by the widespread occurrence of hydrated silica deposits in fluviolacustrine and groundwater-influenced settings(Pan et al 2021).…”
mentioning
confidence: 99%